The integrative activity program as evaluated and implemented by teachers in the service - Sugue, Florencia S. 1919- (1960)
The purpose of this study is to present the ideas of teachers who evaluated the growth and development of their knowledge on integrative techniques through the summer observation and participation classes in the Philippine Normal College. This further shows the ideas of teachers regarding their role in the guidance of unit activities in the classroom during observational activities and workshops. Lastly, the study presents the influences of these insights to the teachers and the practical applications of these in the field.
Thesis (M.Ed.)--University of the Philippines, 1960
Typescript (carbon copy)
Vita.
Keywords: Education, Elementary